Case report: Corticosteroids as an adjunct treatment for the management of liver abscess in Papillon–Lefèvre syndrome: A report on two cases - Basu, Suprit; Tyagi, Reva; Jindal, Ankur Kumar; Medha, Apurva; Banday, Aaqib Zaffar; Babbar, Alisha; Sharma, Apoorva; Mahajan, Rahul; Vignesh, Pandiarajan; Rawat, Amit (Frontiers in Pediatrics, 2022)
Papillon–Lefèvre syndrome (PLS) is a rare autosomal recessive disorder characterized clinically by palmoplantar keratoderma, periodontitis and recurrent pyogenic infections. Liver abscess is rarely reported in these patients. Use of corticosteroids for treatment of liver abscess akin to chronic granulomatous disease has not been reported previously. Here we report 2 cases of liver abscess in PLS that responded to corticosteroids.